Hybrid Firefly Model in Routing Heterogeneous Fleet of Vehicles in Logistics Distribution. (7th April 2015) - Simić, Dragan; Kovačević, Ilija; Svirčević, Vasa; Simić, Svetlana
Abstract : Logistics distribution is adaptive, dynamic and open self-organizing system, which is maintained by flows of information, materials, goods, funds and energy. This article presents biological intelligence for modelling and optimization on vehicle routing problem (VRP) of logistics distribution. The aim of this research is to create a novel hybrid model including genetic and firefly algorithms in routing heterogeneous fleet of vehicles in logistics distribution system. The proposed hybrid model in routing heterogeneous fleet VRP is tested on realistic data set in Serbian company 'Carnex Ltd'. The experimental results of this method are compared with the empirical results and show that the experimental results obtained by new hybrid genetic–firefly model are better then empirical results in the company.